Association of knowledge and attitude with health protocols’ compliance during the COVID-19 pandemic - Chantika Putri Irawan; Soegianto Ali (Atma Jaya Catholic University of Indonesia, 2025)
Introduction: The COVID-19 pandemic negatively impacted the community. The Indonesian government has implemented health protocols to control COVID-19 transmission. Knowledge and attitude affect the compliance level, which plays an important role in the success of health protocol implementation. This study aims to evaluate the knowledge, attitude, and compliance towards COVID-19 control protocols in Indonesia, as well as factors that influence the knowledge. The findings can be used in formulating a strategy to reduce COVID-19 transmission or other infectious diseases in Indonesia. Methods: A cross-sectional study utilizing a purposive snowball sampling method was performed by distributing a Google form questionnaire through social media from June to August 2021. The target population was all Indonesians aged ≥17 years old who were present in Indonesia during the pandemic and had access to the questionnaire. Incomplete questionnaires were excluded. The data were analyzed descriptively and statistically using the Chi-square or Fisher’s exact test. Results: Out of 713 respondents who met the study criteria, 95% had adequate knowledge, 87% exhibited a positive attitude, and 79.7% adhered to health protocols with high compliance. Knowledge significantly influenced attitude to COVID-19 (p<0.001). Additionally, sufficient knowledge (p<0,001; OR 9.19, 95% CI 4.47-18.88) and positive attitudes (p<0,001; OR 19.18; 95% CI 11.44-32.16) showed significant correlation with compliance. Age (p<0.001), education level (p<0.001), experience (p=0.018), and duration of social media usage (p=0.004) were significantly associated with knowledge. Conclusion: The Indonesian community generally has adequate knowledge and a positive attitude toward COVID-19. This could significantly improve compliance to health protocols.